Correlation between central venous and mixed venous oxygen saturation in the elective abdominal aortic aneurysm surgery - Šoškić, Ljiljana; Kočica, Mladen; Cvetković, Dragan; Miličić, Biljana; Ladjevic, Nebojsa; Palibrk, Ivan; Karadžić, Milica; Grujić, Miloš; Vještica-Mrdak, Milica; Ristić, Arsen (Vojnosanitetski pregled, 2021)
Background/Aim. The concept of utilizing central venous oxygen saturation (ScvO2) to calculate cardiac index (CI) remains controversial and neither precise nor generally applicable conclusion has been reached yet. We evaluated the relationship between ScvO2 and mixed venous oxygen saturation (SvO2) in elective surgery of the abdominal aorta. The adequacy of their interchangeability was tested by comparing cardiac indices (CI) calculated by two methods in patients that underwent major vascular surgery. The aim of this study was to test the correlation between ScvO2 and SvO2 in different time frames, in patients undergoing elective abdominal aortic aneurysm (AAA) surgery as well as to determine if the use of ScvO2 for calculating CI by the modified Fick equation, could be feasible and accurate surrogate for the values obtained by pulmonary artery catheter (PAC). Methods. This prospective observational study included 125 consecutive patients that underwent elective AAA surgery. The ScvO2 and SvO2 data, as well as CI values, were obtained and compared from samples taken in three different time frames: immediately after induction of general anesthesia (T0), immediately after admission in the intensive care unit (ICU; T1), and 8 h after admission in the ICU (T2). The Fick equation, used for CI estimation from ScvO2 (CI-F), for the purpose of this study, was simplified according to Walley. Results. There was good linear correlation between ScvO2 and SvO2 in all time frames and linear regression study revealed strongest coefficient of determination (R2 = 0.661) in T2 time-frame. There was no correlation between CI-F (i.e. CI calculated from ScvO2 by modified Fick equation) and CI (measured by PAC from SvO2) in any time-frame. Conclusion. The results of our study confirm that ScvO2 is a reliable substitute for SvO2 among patients undergoing elective surgery of the AAA. However, ScvO2 cannot be used as a surrogate to true SvO2 in the calculation of CI.
Keywords: aorta, abdominal; aortic aneurysm; monitoring, physiologic; oxygen; oximetry